MOBILE APPLICATION DESIGN TO PROMOTE CULTURAL TOURISM IN WEST SUMBA - Rangga, Andreas Ariyanto; Dapadeda, Ardiyanto (Universitas Royal, 2025)
Abstract: West Sumba Regency has many traditional villages, local dances and bu-daya festivals that can be seen as cultural tourist attractions. This is indicated by the increasing number of people visiting cultural tourist attractions in West Sumba. However, there are still few promotional and information services available for tourists related to cultural tourism to visit, such as location information, events and access to cultural tourism spots in West Sumba. Therefore, the purpose of this research is to create a mobile phone-based application that can promote bu-culture tourism in West Sumba Regency. The specific objective is to create a platform that makes it easy for tourists to explore and understand the cultural richness and cultural tourism destinations of West Sumba. This research uses a user-centered design (UCD) approach to create a successful mobile application. This application will help tourists get information about cultural tourism destinations in West Sumba. In addition, the app has additional features, such as maps, traditional villages, local dances, cultural festivals, event schedules and travel agents. Keywords: Cultural Tourism; Design; Mobile Apps; west sumba Abstrak: Kabupaten Sumba Barat memiliki banyak kampung adat, tarian lokal, dan festival budaya yang dapat dilihat sebagai tempat wisata budaya. Ini ditunjukkan oleh peningkatan jumlah orang yang mengunjungi tempat-tempat wisata budaya di Sumba Barat. Namun, masih sedikit layanan promosi dan informasi yang tersedia bagi para wisatawan terkait wisata budaya yang ingin dikunjungi, seperti informasi lokasi, acara dan akses ke tempat-tempat wisata budaya di Sumba Barat. Oleh karena itu, tujuan dari penelitian ini adalah untuk membuat aplikasi berbasis ponsel yang dapat mempromosikan wisata budaya di Kabupaten Sumba Barat. Tujuan khusus adalah untuk membuat sebuah platform yang memudahkan wisatawan untuk mengeksplorasi dan memahami kekayaan budaya dan destinasi wisata budaya Sumba Barat. Penelitian ini menggunakan pendekatan desain berbasis pengguna (UCD) untuk membuat aplikasi mobile yang berhasil. Aplikasi ini akan membantu wisatawan mendapatkan informasi tentang destinasi wisata budaya di Sumba Barat. Selain itu, aplikasi ini memiliki fitur tambahan, seperti peta, kampung adat, tarian lokal, festival budaya, jadwal acara, dan agen perjalanan wisata. Kata kunci: aplikasi seluler; desain; sumba barat; wisata budaya